Prostaglandin E2 Affects Differently the Release of Inflammatory Mediators from Resident Macrophages by LPS and Muramyl Tripeptides - Peter Dieter; Ute Hempel; Sabine Kamionka; Angelika Kolada; Birgit Malessa; Edith Fitzke; Thuy-An (Hindawi Limited, 1999)
LPS and MTP-PE (liposome-encapsulated N-acetylmuramyl-L-alanyl-D-isoglutaminyl-L-alanine-2-:[1',2'-dipalmitoyl-sni-glycero-3-(hydroxy-phosphoryl-oxyl)] etylamide) induce in liver macrophages a synthesis and release of TNF-α, nitric oxide and prostanoids. Both agents induce an expression of mRNA's encoding TNF-α, inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2, and of corresponding proteins. LPS and MTP-PE induce a rapid activation of the extracellular regulated kinase (ERK) isoenzymes-1 and -2. Inhibition of map kinase isoenzymes leads to a decreased release of TNF-α, nitric oxide and prostaglandin (PG) E2 after both agents. The transcription factors NF-κB and AP-1 are strongly activated by LPS within 30 minutes. MTP-PE induces a weak activation of both transcription factors only after 5 hours. Inhibition of NF-κB inhibits the LPS- but not the MTP-PE-induced release of TNF-α, nitric oxide and PGE2. PGE2 release after LPS is higher than after MTP-PE. Exogenously added PGE2 inhibits the activation of map kinase and TNF-α release by LPS, but not by MTP-PE. Release of nitric oxide after LPS and MTP-PE is enhanced after prior addition of PGE2. PGD2 is without any effect. MTP-PE, but not LPS, induces a cytotoxicity of Kupffer cells against P815 tumor target cells. The MTP-PE-induced cytotoxicity is reduced by TNF-α neutralizing antibodies, indicating the involvement of TNF-α. Thus our results suggest that the different potencies of LPS and MTP-PE as immunomodulators probably result from different actions on Kupffer cells, resulting in differences in the amounts and kinetics of released TNF-α and PGE2, and that PGE2 plays an important regulatory role in the action of LPS, but not in the actions of MTP-PE.